2012
DOI: 10.9734/bjemt/2012/1213
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Relationship between Private and Public Investment in Zimbabwe

Abstract: The study examines the relationship between private and public investment in Zimbabwe utilizing yearly time series data for the period 1970 to 2007. Emphasis is placed on the direction of causality and the effect of the two types of investment on each other. The paper constructs empirical models for both private and public investment, based on the flexible accelerator theory. Private investment is found to be cointegrated with public investment. A cointergration approach and VEC model are employed to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, Ndovorwi (1997) used quarterly data, which he interpolated, but Jenkins (1998) used annual data and both studies were for Zimbabwe. Muyambiri, Chiwira, Batuo, and Chiranga (2010) investigated the relationship between public and private investment spending for Zimbabwe, using the Accelerator model and tested Pairwise Granger causality, and found that private investment granger causes public investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Ndovorwi (1997) used quarterly data, which he interpolated, but Jenkins (1998) used annual data and both studies were for Zimbabwe. Muyambiri, Chiwira, Batuo, and Chiranga (2010) investigated the relationship between public and private investment spending for Zimbabwe, using the Accelerator model and tested Pairwise Granger causality, and found that private investment granger causes public investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical evidences show that in some important ways, private investments in developed economies are influenced by different factors than private investments in developing economies. Investigations made by Ahmad and Qayyum (2008), Ghura and Goodwin (2000), Oshikaya (1994), Ramirez (1994) have found that the two types of investment are positively correlated (Muyambiri et al, 2010). Faini (1994) analyzes whether there is a training effect or a substitute (crowding out) effect between public investment and private investment in Africa.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Most of these studies have used time series analysis with a few opting for panel data analysis. The flexible accelerator model was one of the models used to empirically estimate investment behavior (Muyambiri et al, 2010). The accelerator model was propounded by Clark (1917).…”
Section: Introductionmentioning
confidence: 99%